The Major Citrus Cultivars in Spain - Ortiz Marcide, Jesús M.; Zaragoza, Salvador; Bono-Úbeda, Rafael (ASHS, 2022)
Most of the citrus fruit are grown in two regions of Spain: a) the Levante area, which extends along the East coast and includes the provinces of Castellon, Valencia, Alicante, and Murcia, with about 80% of the total plantations; and b) the Andalusian area, with plantings both along the Guadalquivir river in the provinces of Cordoba and Sevilla, and near the coast, mainly in the provinces of Huelva, Malaga, and Almería, the area representing about 15% of the country’s total (4). The rest of citrus area is scattered in many other provinces of Spain (4), mostly near the coast (Fig. 1). Plantings of citrus by varietal groups are listed in Table 1 (5). With respect to the location of production of citrus fruits by groups of varieties (Table 2), most of the sweet oranges and mandarins are grown in the Valencia region (Valencia, Castellon, and Alicante provinces), while lemons are produced mainly in Murcia. The total production is over 3 x 106 1 (8).